Street food : culture, economy, health and governance - De Cassia Vieira Cardoso, Ryzia; Companion, Michele; Marras, Stefano Roberto (London : Routledge, 2014)
'Prepared foods, for sale in streets or markets, are ubiquitous around the world and throughout history. This volume is one of the first to provide a comprehensive social science perspective on street food. It is shown how street foods represent a culturally diverse, multifaceted and economically significant phenomenon, particularly for poor or vulnerable groups, including women and migrants. Other key issues addressed include: policy, regulation and governance of street food and vendors; food safety and health; and the contribution of street food to urban food security. Many chapters provide case studies from specific cities in different regions of the world. These include North America (Los Angeles, New York, Portland, Toronto, Vancouver), Central and South America (Bogota, Buenos Aires, La Paz, Lima, Mexico City, Montevideo, Santiago, Salvador da Bahia, Sao Paolo), Asia (Bangkok, Dhaka, Kathmandu, Kolkata, Penang), Africa (Accra, Abidjan, Bamako, Freetown, Mozambique) and Europe (Amsterdam). Such studies illustrate the immense diversity and economic and cultural significance of street food'--
Includes bibliographical references and index.
Keywords: Restaurants -- Social aspects; Street food; Street-food vendors; Fast Foods; Restaurants; Cultural Characteristics; Food Safety; Nutrition policy; Economics